2022
DOI: 10.3389/fmicb.2022.1025983
|View full text |Cite
|
Sign up to set email alerts
|

A methyltransferase LaeA regulates ganoderic acid biosynthesis in Ganoderma lingzhi

Abstract: The methyltransferase LaeA is a global regulator involved in the biosynthesis of secondary metabolites by ascomycete fungi. However, little is known of its regulatory role in basidiomycete fungi. In this study, the laeA gene was identified in the basidiomycete Ganoderma lingzhi and its function in regulating the biosynthesis of anti-tumor ganoderic acids was evaluated. A laeA deletion (ΔlaeA) Ganoderma strain exhibited significantly reduced concentration of ganoderic acids. qRT-PCR analysis further revealed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…LaeA regulates the expression of multiple secondary metabolic gene clusters and affects the formation of secondary metabolites. Loss of the LaeA gene hindered the expression of multiple secondary metabolic gene clusters, including kojic acid, cyclopiazonic acid, citrinin, citric acid, and the lovastatin gene cluster ( 2 , 30 , 69 71 ). In Valsa mali , about half (31/60) of the secondary metabolism gene clusters are regulated by VmLaeA ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…LaeA regulates the expression of multiple secondary metabolic gene clusters and affects the formation of secondary metabolites. Loss of the LaeA gene hindered the expression of multiple secondary metabolic gene clusters, including kojic acid, cyclopiazonic acid, citrinin, citric acid, and the lovastatin gene cluster ( 2 , 30 , 69 71 ). In Valsa mali , about half (31/60) of the secondary metabolism gene clusters are regulated by VmLaeA ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been commonly observed that the overexpression of LaeA has been successfully used to activate some gene clusters, enhance production of several secondary metabolites, and produce new compounds in fungi ( 45 ). Overexpression of LaeA increases the transcription and product formation of genes involved in the kojic acid antitumor compounds terrequinone A, cyclopinionic acid, and tertrimilone ( 2 , 30 , 69 72 ). Moreover, overexpression of LaeA results in the production of the novel compound in Aspergillus versicolor 0312 ( 73 ), Chaetomium globosum ( 29 ), and Penicillium dipodomyis YJ-11 ( 74 ), respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lanosterol synthase (LS), farnesyl pyrophosphate synthase (FPS), 3-hydroxy-3-methyl-glutaryl-CoA reductase (HMGR) and squalene synthase (SQS) are the key enzymes in the ganoderic acid synthesis pathway ( Shi, Ren, Mu, & Zhao, 2010 ). The synthesis of lanosterol from 2,3-epoxysqualene is catalyzed by LS, and the expression of lanosterol synthase gene and the content of ganoderic acid are positively correlated ( Luo, Li, & Xu, 2022 ). LaeA is a global regulatory gene, and the production of ganoderic acid is positively correlated with the transcription level of LaeA gene ( Luo et al, 2022 ).…”
Section: Biosynthetic Pathways Of Ganoderic Acidmentioning
confidence: 99%
“…The synthesis of lanosterol from 2,3-epoxysqualene is catalyzed by LS, and the expression of lanosterol synthase gene and the content of ganoderic acid are positively correlated ( Luo, Li, & Xu, 2022 ). LaeA is a global regulatory gene, and the production of ganoderic acid is positively correlated with the transcription level of LaeA gene ( Luo et al, 2022 ). HMGR is the rate-limiting enzyme which is responsible for catalyzing the reduction of 3-hydroxy-3-methylglutaryl-CoA (HMG-CoA) to mevalonate ( Zhao, Zhong, Liang, Wang, & Jong, 2004 ).…”
Section: Biosynthetic Pathways Of Ganoderic Acidmentioning
confidence: 99%